2021
DOI: 10.1101/2021.04.06.438630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADNKA overcomes SARS-CoV2-mediated NK cell inhibition through non-spike antibodies

Abstract: SARS-CoV-2 antagonises the cellular interferon response, but whether the virus manipulates cellular immunity is unclear. An unbiased proteomic approach to determine how cell surface protein expression is altered on SARS-CoV-2-infected lung epithelial cells showed downregulation of activating NK cell ligands: B7-H6, MICA, ULBP2, and Nectin1, but no effect on surface MHC-I expression. NK ligand downregulation correlated with a reduction in NK cell activation by infected cells, and was overcome by antibody-depend… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 96 publications
(150 reference statements)
1
11
0
Order By: Relevance
“…In addition, several studies have shown that the magnitude of the MBC response to SARS-CoV-2 continues to increase beyond 6 months ( 9 , 23 , 51 , 62 ), again implying that we may have underestimated the extent of recall potential in our cohort at 5 months. Future studies should also examine the preservation of non-spike-specific MBCs with the potential to produce Abs mediating antiviral effects beyond neutralization, since other viral proteins (ORF3a, membrane and nucleocapsid) can play a dominant role in triggering Ab-dependent NK cell activation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that the magnitude of the MBC response to SARS-CoV-2 continues to increase beyond 6 months ( 9 , 23 , 51 , 62 ), again implying that we may have underestimated the extent of recall potential in our cohort at 5 months. Future studies should also examine the preservation of non-spike-specific MBCs with the potential to produce Abs mediating antiviral effects beyond neutralization, since other viral proteins (ORF3a, membrane and nucleocapsid) can play a dominant role in triggering Ab-dependent NK cell activation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 While most studies have focused on the Fc effector functions of S‐specific antibodies, the M, N, and ORF3a proteins can all be detected on the surface of infected cells and be targeted by antibodies that mediate NK cell activation. 14 While it remains unclear the degree to which ADCC and ADP contribute to protection against SARS‐CoV‐2 in humans, several viral challenge studies in mice have shown the protective value of many RBD‐ and NTD‐specific mAbs relies upon engagement with cellular Fc receptors in vivo. 15 , 16 , 17 …”
Section: Overview Of Humoral Immunity To Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…Future studies should also examine the preservation of non-spike-specific MBC with the potential to produce antibodies mediating antiviral effects beyond neutralisation, since other viral proteins (ORF3a, membrane and nucleocapsid) can play a dominant role in triggering antibody-dependent NK cell activation. 62 In conclusion, by focusing on an elderly cohort with a high proportion of nAb loss, we demonstrated that this waning in the first line of humoral defence can be compensated by the presence of a reserve of adaptive B cell memory in the majority of cases. Our findings highlight the importance of including measures of B cell memory in larger studies of natural infection and vaccination to determine their role as additional correlates of protection.…”
Section: Discussionmentioning
confidence: 69%
“…Future studies should also examine the preservation of non-spike-specific MBC with the potential to produce antibodies mediating antiviral effects beyond neutralisation, since other viral proteins (ORF3a, membrane and nucleocapsid) can play a dominant role in triggering antibody-dependent NK cell activation. 62…”
Section: Discussionmentioning
confidence: 99%